If kids ruled the world, how would they stop the non-medical use of prescription drugs? - Mirsada Serdarevic; Vicki Osborne; Amy Elliott; Catherine W Striley; Linda B Cottler (College of Public Health Sciences, Chulalongkorn University, 2020)
Purpose - This study examined how youth would mitigate non-medical use of prescription medication among their peers. Design/methodology/approach - The National Monitoring of Adolescent Prescription Stimulants Study (N-MAPSS) was conducted as an interview comprising 11,048 youth of 10-18 years of age between 2008 and 2011 from entertainment venues of 10 US urban, suburban, and rural areas. Using a mixed-methods approach, participants completed a survey culminating in open-ended questions asking: (1) How should kids your age be informed about prescription drugs and their effects? (2) If you ran the world, how would you stop kids from taking other people's prescription medicines? (3) Why do people use prescription stimulants without a prescription? Responses from a random sample of 900 children were analyzed using qualitative thematic analyses. Findings - The random sample of 900 youth (52 percent female, 40 percent white, with a mean age of 15.1 years) believed they should be educated about prescription drugs and their negative effects at schools, at home by parents, through the media, and health professionals. Youth would stop kids from using other people's prescription drugs through more stringent laws that restricted use, and providing education about negative consequences of use. Peer pressure was the most common reason the youth gave for using other's pills, though some reported taking them out of curiosity. Originality/value - The importance of considering youth's opinions on non-medical use of prescription medications is often overlooked. This evidence, from a peer perspective, could end the illicit use of prescription drugs among today's youth.